STUDI KASUS ANALISIS ASUHAN KEPERAWATAN PADA PASIEN DENGAN DIABETES MELITUS TIPE 2 DI RUMAH SAKIT X - Albertha Kurniati Harai; Lia Natalia (Forind Press, 2026)
Type 2 diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels due to impaired insulin function or production, which may lead to complications if not properly managed. This paper aims to examine nursing care in two patients with type 2 diabetes mellitus using a case study method based on a systematic nursing process approach.Data were collected through observation, interviews, physical examinations, and documentation studies to formulate nursing diagnoses, including unstable blood glucose levels, ineffective airway clearance, ineffective peripheral perfusion, and hypervolemia. The implementation results showed significant clinical progress, characterized by the stabilization of the patients' general condition and a decrease in Random Blood Glucose (RBG) levels from an initial 298 mg/dL to 186 mg/dL, accompanied by a reduction in complaints of nausea and fatigue. Furthermore, regarding the issue of ineffective airway clearance, patients demonstrated a better ability to expectorate secretions, reduced coughing frequency, and a decrease in adventitious breath sounds such as crackles (rhonchi). The evaluation of nursing care for these two patients with Type 2 Diabetes Mellitus comorbidities indicated clinical improvement meeting the expected outcomes, evidenced by reduced symptoms, more stable vital signs, better-controlled blood glucose levels, and improved respiratory function and secretion clearance, proving that the nursing care provided was effective in enhancing the patients' health status.